Literature, or the travelling tattoo - Julia L. Frengs (Francosphères)
This essay considers Kanak author Déwé Gorodé’s 2009 novel Graines de pin colonnaire and Tahitian author Stéphanie Ari’irau Richard’Vivi’s 2006 novel Matamimi, ou La vie nous attend as ‘mobile manuscripts’: dialogic, literary border-crossings that facilitate communication and connections in Oceania. The boundary-crossing, permeable characteristics of the Oceanian tattoo as conceptualized in the works of Sean Mallon, Albert Wendt, and Margo DeMello provide a metaphorical lens through which I suggest we regard the corporeal literary engagement of the two Oceanian women authors examined here. Envisioned as coterminous with the tattoo, Oceanian literature is endowed with similar boundary-transcending functions: it travels, influences, and becomes informed by its connections with other bodies and world literatures, enabling an international dialogue between writers, within Oceania and beyond. The study demonstrates how Gorodé and Ari’irau employ socially inscribed, marked bodies to participate in an inter-Oceanic conversation that textually reinforces their mutual concern for a continued effervescence of an Oceanian literary tradition in French.